Implementación de una máquina amasadora de arcilla para la Asociación de Productores y artesanos La Victoria del cantón Pujilí. - Toapanta Vargas, Marco Rolando (2018)
At present, La Victoria Parish at Pujilí Canton is well known for its pottery; the manufacturing of crafts from clay has a high acceptance inside and outside the country, becoming the source of work for most of the inhabitants, but this activity requires of a lot of time and physical effort for both artisans, and rudimentary machines, one of the processes at the elaboration of crafts is the kneading of the clay where the material is placed in water and later with a softening technique it becomes a compact mass. The implementation of a clay kneading machine allows improving the conditions of the kneading of this material that is currently done with the feet, and it takes time to obtain the appropriate mass. The objectives that allow its development will be the collection of information regarding this process and testing using a prototype that supports the design parameters and the selection of materials. In the absence of scientific documentation about this type of machines, it is necessary to apply the experimental method and obtain as a result that the clay kneading work can be carried out with 450 revolutions/minute using a 1Hp motor, which facilitates the calculation of the torque; also through the use of equations, calculations were made to reduce the number of revolutions to which the kneading machine works best, that is implemented to obtain a 2 Hp motor efficiency and reducing the number of revolutions/minute to 100 using transmission elements such as pulleys and sprockets. Through the implementation, the result is: there is a greater amount of production in a shorter time and physical effort, thus being of great benefit to the artisanal sector.